Lablab Purpureus Influences Soil Fertility and Microbial Diversity in a Tropical Maize-Based No-Tillage System - Patricia Dörr de Quadros; Adam R. Martin; Kateryna Zhalnina; Raquel Dias; Adriana Giongo; Roberta Fulthorpe; Cimelio Bayer; Eric W. Triplett; Flávio A. de O. Camargo (Soil Systems, 2019)
There are multiple mechanisms by which enhanced diversity of plant communities improves soil structure and function. One critical pathway mediating this relationship is through changes to soil prokaryotic communities. Here, nine different cropping systems were studied to evaluate how legume and grass cover crops influence soil fertility and microbial communities in a maize-based no tillage system. The soil’s bacterial and archaeal communities were sequenced (Illumina GAIIx, 12 replicates for treatment) and correlated with eight different soil features. The microbial community composition differed widely between planting treatments, with three primary “community types” emerging in multivariate space: (1) A community type associated with bare soil linked with low P, low pH, and high aluminum [Al]; (2) a community type associated with Lablab beans linked with high soil N, total organic carbon and other base cation concentrations, and high pH; and (3) a community type of all other non-lablab planting arrangements linked with higher soil P (relative to bare soil), but lower soil fertility (N and base cations). Lablab-based arrangements also expressed the highest microbial richness and alpha diversity. The inclusion of Lablab in maize-based cropping systems represents a potential alternative to reduce the use of chemical fertilizers and increase the chemical and biological quality in agricultural soils under the no-tillage system.